EGMR 60202/15 vom 6. Oktober 2020 , CASE OF I.S. v. SWITZERLAND - [German Translation] summary by the Austrian Institute for Human Rights (ÖIM) - Hudoc Ch (2020)
Violation of Article 5 - Right to liberty and security (Article 5-1-b - Lawful order of a court;Non-compliance with court order;Secure fulfilment of obligation prescribed by law;Article 5-1-c - Bringing before competent legal authority;Reasonable suspicion;Reasonably necessary to prevent fleeing;Reasonably necessary to prevent offence);Non-pecuniary damage - award (Article 41 - Non-pecuniary damage;Just satisfaction); Violation: 5;5-1-b;5-1-c